ANALYSIS OF LINGUOCREATIVE STRATEGIES IN MODERN MEDIA TEXTS (Scientific journal of the Fergana State University, 2025)
The article explores the linguocreative strategies used in modern media texts. It examines the linguistic techniques that create emotional and cognitive effects on the audience. The study analyzes the role of lexical, grammatical, and stylistic devices in shaping the unique style of media content. The practical significance of the work lies in the potential application of the findings for developing effective communication strategies in the media sphere.